Participatory climate-service and information training in Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
One year ago, a team of researchers from the University of Reading, in UK, and local partners in Tanzania, organised a number of participatory trainings for smallscale farmers on climate-services and information. The trainings were held in villages outside of Dodoma, Tanzania, which is a very arid and dry part of the country. The team recently re-visited two of the farmer groups, to see what they had learned during the 4-day training session, what they felt was useful and if anything happened after the trainings, eg. did they change crops or planting practices? The trainings introduced the concept of climate change, rainfall variability, and presented the country’s historical rainfall data and forecasts. The trainings also showed farmers how to, based on crop, temperature and rainfall information, calculate risks and probabilities of crops failure, while identifying which crops could work well in their area. The trainings provided a list of suitable crops, but it was the farmers who in the end decided if and how they wanted to implement what they had learned, or not. This to ensure ownership and making sure any choice made is grounded in farmers’ own realities. These photos are from the revisit session, held in October of this year in Makoja, Tanzania. Stay tuned on CCAFS blog to see if the farmers had made any changes to their farming practices or not. This participatory project is supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS): www.ccafs.cgiar.org/blog. Photo: Cecilia Schubert (CCAFS)